Asymptomatic sustained ventricular fibrillation in a patient with left ventricular assist device - Busch, Mathias C.; Haap, Michael; Kristen, Arnt; Haas, Christian S. (Annals of emergency medicine, 2011)
Optimal medical treatment, cardiac resynchronization, and the use of an implantable cardioverter defibrillator are established therapies of severe congestive heart failure. In refractory cases, left ventricular assist devices are more and more used not only as bridging to cardiac transplantation but also as destination therapy. Ventricular arrhythmias may represent a life-threatening condition and often result in clinical deterioration in patients with congestive heart failure. We report a case of asymptomatic sustained ventricular fibrillation with preserved hemodynamics caused by a nonpulsatile left ventricular assist device. Consecutive adequate but unsuccessful discharges of the implantable cardioverter defibrillator were the only sign of the usually fatal arrhythmia, prompting the patient to consult emergency services. Electrolyte supplementation and initiation of therapy with amiodarone followed by external defibrillation resulted in successful restoration of a stable cardiac rhythm after 3.5 hours.
Available online 31 July 2010
Gesehen am 24.06.2022